Golda Meir's foreign decision-making process : an analysis - Asaf, Michal Kremer (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
"This book focuses on the analysis of Golda Meir's foreign decision making processes during her tenure as Prime Minister (1970-1973), offering three unique case studies. It exposes the political-diplomatic aspects of foreign policy, using interviews and analysis of hundreds of formerly secret documents from various national archives. Furthermore, it proposes a new, innovative form of analysis, termed the Holistic Combined Spiral Model (HCSM), based on exploring foreign decision making processes through the four leading existing theoretical approaches, namely rational, emotional, bureaucratic and irrational factors. The study explores the fields of leadership, government and foreign decision making through a holistic perspective in two integrated dimensions: first, the decision making process during periods of crisis, such as the Yom Kippur War, and, second, external influences, such as the relationships with the American government and between the superpowers. Furthermore, after revealing and analysing the factors and components of the foreign decision making process, this book appreciates the complexity of these processes, which, during the dynamic and changing times in which we live, world leaders have to master."--
Incluye referencias bibliográficas pages [293]-310 and index.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Meir, Golda, -- 1898-1978.; Israel -- Foreign relations -- History -- 20th century; Libros electrónicos.